2006
DOI: 10.1111/j.1442-2042.2006.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic acid ingestion promotes renal stone formation in rats treated with vitamin D3

Abstract: Objective: Although hypercalciuria, a well-established adverse effect of vitamin D3, can be a risk factor of renal stone formation, the risk of nephrolithiasis has not been well defined. The consumption of a diet high in acid precursors is often cited as a risk factor for the development of calcium-based kidney stones. In the present study, we investigated the effect of chronic acid ingestion on kidney stone formation in rats treated with calcitriol (1-25[OH]2 D3). Methods: Control rats (C-C), calcitriol-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Whether 1,25D treatment leads to reduced proximal tubule citrate reabsorption is not known. Okamoto et al (77) found a trend to higher U citrate in male Wister rats treated with 1,25D. While studies in humans demonstrated a link between VDR polymorphisms and tubular reabsorption of citrate (62, 73), we are not aware of any studies directly linking 1,25D levels and citrate excretion.…”
Section: Discussionmentioning
confidence: 74%
“…Whether 1,25D treatment leads to reduced proximal tubule citrate reabsorption is not known. Okamoto et al (77) found a trend to higher U citrate in male Wister rats treated with 1,25D. While studies in humans demonstrated a link between VDR polymorphisms and tubular reabsorption of citrate (62, 73), we are not aware of any studies directly linking 1,25D levels and citrate excretion.…”
Section: Discussionmentioning
confidence: 74%
“…However, inconsistent results have been reported. 25 To our knowledge, no studies have examined urinary FE of electrolytes in goats fed grass hay with or without supplemental ammonium chloride. 18 Also, changes in bone morphology and subsequent osteopenia associated with dietary-induced metabolic acidosis in sheep have been reported.…”
mentioning
confidence: 99%
“…One study suggested that a high‐protein, high‐sodium diet in postmenopausal women, considered typical for many women in the USA, detrimentally affects calcium and bone metabolism in those with a certain vitamin D‐receptor genotype [15]. A recent study in rats showed that hypercalciuria occurred with vitamin D treatment only when they were fed a chronic high dietary acid load, suggesting that vitamin D treatment, even in high dosages, does not lead to hypercalciuria unless other dietary risk factors are present [16]. Given these data, we theorise that the risk of hypercalciuria from vitamin D supplementation, using accepted blood measures of vitamin D adequacy as outcome variables, might be smaller than the risks from innumerable different combinations of genetic and dietary alterations that could contribute to altered calcium transport in the intestine, kidney and bone [17].…”
Section: Discussionmentioning
confidence: 99%